2024
DOI: 10.1007/s00520-023-08280-7
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood events and mental health problems in cancer survivors: a systematic review

Chris Hinnen,
Emma von Haeseler,
Frederiek Tijssens
et al.

Abstract: Purpose The purpose of this study was to systematically review the literature on the association between adverse childhood events (ACEs) and mental health problems in cancer survivors. Methods This review was conducted in line with PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Four databases (PubMed, PsychINFO, Web of Science, and Cochrane) were searched on 27–08-2023. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…To the best of our knowledge, this is the first study conducted among adult cancer survivors investigating the relationship between ACEs and three health-risk behaviors (cigarette smoking, e-cigarette smoking and binge alcohol drinking) using population-based, nationally representative data. Approximately, 63% of our sample have self-reported ACE which falls within the range provided by a recent systematic review [ 38 ]. This review reported from 40% to 95.5% prevalence rate of ACE among cancer survivors [ 38 ].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…To the best of our knowledge, this is the first study conducted among adult cancer survivors investigating the relationship between ACEs and three health-risk behaviors (cigarette smoking, e-cigarette smoking and binge alcohol drinking) using population-based, nationally representative data. Approximately, 63% of our sample have self-reported ACE which falls within the range provided by a recent systematic review [ 38 ]. This review reported from 40% to 95.5% prevalence rate of ACE among cancer survivors [ 38 ].…”
Section: Discussionmentioning
confidence: 98%
“…Approximately, 63% of our sample have self-reported ACE which falls within the range provided by a recent systematic review [ 38 ]. This review reported from 40% to 95.5% prevalence rate of ACE among cancer survivors [ 38 ]. Consistent with the existing evidence [ 39 , 40 ], our findings also noted that emotional abuse is the most frequently reported ACE.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation